Family Harmony in Shaping Adolescents’ Social Patterns: A Review of Literature Studies - Muhammad Alridho Lubis; Dinny Rahmayanty; Kheylyla Adha Pierda; Dania Riski Rahayu; Sinta Nurzulina Putri (Universitas Muhammadiyah Enrekang, 2023)
A family that lives side by side with an abundance of love from each member can be used as a picture of a harmonious family. Many people define a harmonious family as happiness that every human dreams of. The presence of a harmonious family certainly creates positive behavior and character of family members. In this regard, the social patterns that teenagers have are largely influenced by factors such as the atmosphere within the family. The purpose of writing this article is to discuss how family harmony plays a role in forming adolescent social patterns. The method used is a literature study that raises a topic similar to the discussion in this article. The findings obtained are in the form of influences on teenagers’ relationships that arise when the family is in a state of harmony and disharmony.